From Field to Table: The Pukekohe Dehydration Factory in the 1940s - Francesco, Cara (Architectural History Aotearoa, 2024)
In August 1943, the New Zealand Governmentʹs Internal Marketing Division announced plans to construct a vegetable dehydration factory in Pukekohe, on the outskirts of southern Auckland. The factory was built with urgency, to dehydrate, quick‐freeze, can and cool store large quantities of vegetables to assist in providing food for United States troops, stationed in the Pacific. The factory consisted of a large, long main factory building, a boiler house and machine shop, a cafeteria, a chemical building, a vinery building, a laboratory, and an administration block. It incorporated the most modern equipment and processing methods of the time, with much of the machinery supplied from the United States. To supply the large quantities of vegetables required under direction from the Department of Agriculture, produce was grown through a combination of state gardens and commercial market gardeners. To meet the demand, the factory operated long hours, becoming a significant local employer, particularly for women. Workers were also deployed from further afield to achieve the necessary processing outputs. This paper examines the development and operation of the Pukekohe Dehydration Factory in the 1940s, its role in supporting the war effort during the Second World War, and its utilisation throughout the remainder of the decade.